International Comparisons of Welfare and Poverty: Generalized Lorenz Orderings for Ten Countries - John A. Bishop; M. John P. Formby; W. James Smith (Luxembourg Income Study (LIS), 1990)
This paper applies generalized Lorenz analysis to income distributions of ten countries using advanced statistical procedures to construct confidence bands around estimates and to generate truncated generalized Lorenz curves to construct a poverty ordering of the countries.
Keywords: 330; Lebensstandard; Armut; Einkommensverteilung; Theorie